2021
DOI: 10.1039/d1re00250c
|View full text |Cite
|
Sign up to set email alerts
|

An activated carbon fiber supported Fe2O3@bismuth carbonate heterojunction for enhanced visible light degradation of emerging pharmaceutical pollutants

Abstract: Development of broadband light harvesting heterojunction via interface tuning over a flexible support has practical wastewater treatment application. Immobilization of the heterojunction over a flexible support like activated carbon fiber...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…It was reported that Kar et al [ 134 ] constructed heterojunctions (Fe 2 O 3 @BC) on ACFs, which could exhibit excellent photocatalytic activities for the degradation of antibiotics under visible light. Furthermore, Jiang et al [ 135 ] deposited spinel-type CoFe 2 O 4 on ACFs.…”
Section: Reuse Of Rcfs In Photocatalysismentioning
confidence: 99%
“…It was reported that Kar et al [ 134 ] constructed heterojunctions (Fe 2 O 3 @BC) on ACFs, which could exhibit excellent photocatalytic activities for the degradation of antibiotics under visible light. Furthermore, Jiang et al [ 135 ] deposited spinel-type CoFe 2 O 4 on ACFs.…”
Section: Reuse Of Rcfs In Photocatalysismentioning
confidence: 99%
“…A number of heterojunction catalysts have been recently reported for the removal of water hyacinth and pharmaceutical pollutants. The applicability of photocatalytic degradation of organic dye pollutants in wastewater management by semiconductors like TiO 2 , ZnO, and SnO 2 is limited as they absorb only a small part of the solar spectrum. Thus, the development of photodegradation of dye by utilizing visible light has recently become an important topic of research.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, as a consequence of anthropogenic activities, many active pharmaceutical ingredients are present in various aqueous matrix waters such as wastewater (from hospitals and urban areas), surface water, and groundwater [ 1 ]. Although they have been spotted at low concentrations, with the range from ng to μg, there are indications that they may be toxic to living organisms [ 2 , 3 , 4 ]. Moreover, to complicate this environmental situation, the removal efficiency of pharmaceuticals in Waste Water Treatment Plants (WWTP) is variable and some of these compounds pass through these plants almost intact [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%